Development and Validation of the Consumer Health Activation Index. (April 2018) - Wolf, Michael S.; Smith, Samuel G.; Pandit, Anjali U.; Condon, David M.; Curtis, Laura M.; Griffith, James; O'Conor, Rachel; Rush, Steven; Bailey, Stacy C.; Kaplan, Gordon; Haufle, Vincent; Martin, David
Background. Although there has been increasing interest in patient engagement, few measures are publicly available and suitable for patients with limited health literacy.Objective. We sought to develop a Consumer Health Activation Index (CHAI) for use among diverse patients.Methods. Expert opinion, a systematic literature review, focus groups, and cognitive interviews with patients were used to create and revise a potential set of items. Psychometric testing guided by item response theory was then conducted among 301 English-speaking, community-dwelling adults. This included differential item functioning analyses to evaluate item performance across participant health literacy levels. To determine construct validity, CHAI scores were compared to scales measuring similar personality constructs. Associations between the CHAI and physical and mental health established predictive validity. A second study among 9, 478 adults was used to confirm CHAI associations with health outcomes.Results. Exploratory factor analyses revealed a single-factor solution with a 10-item scale. The CHAI showed good internal consistency (alpha = 0.81) and moderate test–retest reliability (ICC = 0.53). Reading grade level was found to be at the 6 th grade. Moderate to strong correlations were found with similar constructs (Multidimensional Health Locus of Control, r = 0.38, P < 0.001; Conscientiousness, r = 0.41, P < 0.001). Predictive validity was demonstrated through associations with functional health status measures (depression, r = −0.28, P < 0.001; anxiety, r = −0.22, P < 0.001; and physical functioning, r = 0.22, P < 0.001). In the validation sample, the CHAI was significantly associated with self-reported physical and mental health ( r = 0.31 and 0.32 respectively; both P < 0.001).Conclusions . The CHAI appears to be a valid, reliable, and easily administered tool that can be used to assess health activation among adults, including those with limited health literacy. Future studies should test the tool in actual use and explore further applications.